Geochronology and geochemistry of the tabaquito batholith (Frontal cordillera, argentina): Geodynamic implications and temporal correlations in the sw gondwana margin - Moreno Moreno, Juan Antonio (2019)
The Tabaquito batholith (Frontal Cordillera, western Argentina), is mainly composed of shallowly emplaced granodiorite to minor monzogranite with abundant mafic microgranular enclaves. New sensitive high-resolution ion microprobe U–Pb zircon ages of c. 337 Ma (biotite granodiorite) and c. 284 Ma (mafic dyke) along with previously published geochronological data suggest that a long-lived magmatic system formed through at least two magmatic pulses at c. 337 and c. 322 Ma with later superimposition of Permian magmatism. The Tabaquito granitoids are metaluminous, calc-alkalic and magnesian with I-type affinity. Elevated Th/Nb, Y/Nb and La/Nb ratios along with negative Nb–Ta and positive Pb anomalies are consistent with a continental arc setting. Hf, Nd and Sr isotopic composition of the Tabaquito granitoids suggests that their source could result from mixing of an old felsic crustal component and a juvenile mafic to intermediate component. New geochronological and geochemical data together with published data reveal a continuous arc setting from the Carboniferous to the Permian in Argentina, and important magmatic compositional variations through time and space controlled by episodic fluctuations in the subduction angle of the oceanic plate. Reported and compiled data allow us to infer the continuity of the Carboniferous magmatic arc along the west margin of Gondwana.